Introducing Interculturality into Corporate Communication University Courses in the Czech Republic and Malaysia – A Comparative Study - Marcel Pikhart,; BT Habil, Hadina (Technium Social Sciences Journal, 2020)
The article focuses on the results of implementing intercultural issues into two subjects of corporate communication at the Faculty of Informatics and Management, the University of Hradec Kralove, the Czech Republic in the school year 2019/2020, and at the Language Academy, Faculty of Social Sciences and Humanities, Universiti Teknologi, Malaysia in the Semester 1, 2019/2020. The topic of interculturality, in all its various facets, has recently become very important due to increased global business trade, and therefore, needs the undivided attention of university curricula makers. Therefore, the tutors of the courses of corporate communication decided to introduce the topic of interculturality into the university curricula so that the participants of the courses would be well informed and trained on current trends in intercultural business communication in the global world that has recently become very diverse and hence intercultural. The article describes the nature of implementing new intercultural business communication trends and particular topics introduced into the courses, and the paper attempts to highlight their importance in university curricula. It is a case study from both Europe and Asia as it brings real-life university scenarios that could prove helpful for other designers and tutors of similar courses, such as business communication, managerial communication, corporate communication, intercultural training courses, etc.